The Danish Cerebral Palsy Follow-up Program - Rasmussen, Helle Mätzke (Clin Epidemiol, 2016)
AIM OF DATABASE: The Danish Cerebral Palsy Follow-up Program is a combined follow-up program and national clinical quality database that aims to monitor and improve the quality of health care for children with cerebral palsy (CP). STUDY POPULATION: The database includes children with CP aged 0–15 years and children with symptoms of CP aged 0–5 years. MAIN VARIABLES: In the follow-up program, the children are offered examinations throughout their childhood by orthopedic surgeons, physiotherapists, occupational therapists, and pediatricians. Examinations of gross and fine motor function, manual ability, muscle tone, passive range of motion, use of orthotics, and assistive devices are performed once a year; radiographic examination of the hips is planned based on the child’s age and gross motor function; and the diagnosis is performed once before the age of 5 years. Six indicators were developed based on scientific literature and consensus in the steering committee, and their calculation is based on the following four main variables: radiographic examination of the hip, gross motor function, manual ability, and diagnosis. DESCRIPTIVE DATA: The 2014 annual report includes results of the quality indicators in three of five regions in Denmark comprising 432 children with CP, corresponding to a coverage of 82% of the expected population. CONCLUSION: The Danish Cerebral Palsy Follow-up Program is currently under development as a national clinical quality database in Denmark. The database holds potential for research in prevalence, clinical characteristics of the population, and the effects of prevention and treatment.